Entrepreneurial Practices as a Panacea for Unemployment in Nigeria - Vincent I.O, ODIRI; Joy , MACAULAY, (International Journal of Scientific Research and Management (IJSRM), 2022)
This study investigated whether entrepreneurial practices serve as a panacea for unemployment in Nigeria using the descriptive survey design. Primary data (questionnaire) was the major instrument of data collection, which was administered on 276 respondents out of which 263 questionnaire were fully retrieved. The respondents were made up of successful listed entrepreneurship ventures in Bayelsa and Delta States, Nigeria.  The dependent variable is management of unemployment while the independent variables are entrepreneurial practices (such as time management, strategic thinking, resilience and trend adjustment). Cronbach alpha (a) reliability test was used in validating the research instrument of the study, yielding a Cronbach Alpha of 0.78. Data obtained were analyzed using descriptive statistics (simple percentages and mean responses). Given the analysis, it was found that entrepreneurial practices serve as a panacea for unemployment in Nigeria. Based on the findings of this study, it was recommended among others that entrepreneurs should acquire time management skill because it is a core quality of all successful businesses and entrepreneurs should practice long-range planning and have good time attitudes in opening and closing time of their businesses. Also, entrepreneurs should not take decision quickly when confronted with unpleasant situation affecting their businesses; they should apply strategic thinking and foresights in order to make right decisions.